Analisis Rasm Terhadap Manuskrip Al-Qur’an Kuno Karya Syaikh Ibrahim Mufti di Surau Tuo Kabupaten Lima Puluh Kota - Nadia Sari; Jusnita; Bilfahmi Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Details of writing the mushaf, such as the use of rasm, qira'at, dhabit, are important components in writing the Qur'an. However, discussions regarding the details of writing the Koran have not received much attention from researchers. One of them is research on rasm, some research that discusses rasm only reaches the analysis of specifications and what factors influence the analysis. If we enter the Indonesian archipelago, this can be related to the spread of the use of the Arabic-Pegon script. So the rasm study here will be very interesting because it relates to the ancient manuscript by Shaykh Ibrahim Mufti which is in Surau Tuo, Nagarai Taram. This research aims to analyze the characteristics of rasm used in manuscripts by Shaykh Ibrahim Mufti, as well as understand its significance in the style of writing the Koran in Indonesia. The method used is a qualitative type with a philological analysis approach that focuses on manuscript texts. As well as other supporting sources, such as books, journal articles and related research. The findings of the study show that, although most of the writing follows the rules of Ottoman rasm, there is an inconsistency with the use of rasm imla'I in some pronunciations. Further research can be carried out by continuing the study of the philological approach to all parts of the Qur'an manuscript by Shaykh Ibrahim Mufti, including the parts that have not been completed.